Voter Apathy in the 12th Parliamentary Election of Bangladesh: : Causes and Patterns - Akter, Nazma (The Jahangirnagar Review, 2025)
Voter apathy has become a significant concern in Bangladesh, particularly in the 12th National Parliamentary Election held on January 7, 2024. This study examines the primary causes of voter disengagement, analyzing the socio-political, economic, and institutional factors influencing voter turnout. Using a mixed-method approach, the research incorporates both qualitative and quantitative methodologies, including surveys and Key Informant Interviews (KIIs) with election officials, political analysts, civil society activists, political representatives, journalists, community leaders, and voters. This study seeks to identify specific reasons behind the reluctance of citizens to participate in the voting process. This study will provide an in-depth analysis of these causes and their collective impact on voter apathy, seeking to uncover why certain segments of the Bangladeshi population are disengaged from the voting process. By understanding the root causes, this research aims to propose actionable recommendations to mitigate voter apathy and enhance democratic participation in future elections.